Effect of perioperative remote ischemic conditioning on myocardial injury in patients with unstable angina undergoing percutaneous coronary intervention: protocol of a multicenter, randomized, double-blind clinical trial - Lingfeng Xia; Qingyan Yang; Lingjun Jiang; Yu Zheng; Leilei Chen; Song Lin; Jan D. Reinhardt; Xiao Lu (Trials)
Abstract Background Cardiovascular disease is a leading cause of death, with ischemic heart disease being a significant contributor. While percutaneous coronary intervention (PCI) effectively reduces mortality in myocardial infarction patients, its efficacy for unstable angina (UA) patients is controversial. Complications associated with PCI further limit application in UA. RIC is hypothesized to be an effective co-intervention that reduces PCI-related complications and may potentially enhance the efficacy of the PCI procedure itself. Methods This is a pragmatic, prospective, dual-center, double-blind, randomized controlled clinical trial assessing the effect of remote ischemic conditioning (RIC) during percutaneous coronary intervention (PCI) on injury in unstable angina patients aged ≥ 18 years undergoing coronary angiography. Participants will be randomized to receive either RIC or Sham RIC, in addition to standard pharmacotherapy. Primary outcome includes periprocedural myocardial injury measured by hs-cTnT levels, while secondary outcomes encompass major adverse cardiovascular events, coronary artery lesions Gensini Score, arrhythmia, angina incidence, SAQ scores, ECG changes, and cardiac function assessed by two-dimensional echocardiography. The trial aims to recruit 574 participants and is scheduled to be initiated on 15 January 2024. We will conduct the primary statistical analysis using the intention-to-treat principle. Results from the trial will be presented as comparative summary statistics following the Consolidated Standards of Reporting Trials (CONSORT) guidelines. Trial registration ChiCTR2400079855, 15 January 2024.